Central venous catheter malposition due to dialysis catheter: a case report - Rao, Parnandi Bhaskar (Korean J Anesthesiol, 2016)
A 56-year-old man on maintenance hemodialysis was admitted to the intensive care unit with septic shock and coagulopathy. As there was a dialysis catheter in the right internal jugular vein, the left internal jugular vein was cannulated with a central venous catheter to initiate vasopressor therapy. A chest X-ray showed formation of a catheter loop inside the left brachiocephalic vein, probably due to hindrance by the dialysis catheter. This report describes the hurdles encountered, repeated cannulation attempts, and serial chest X-ray findings required to obtain acceptable placement of the catheter tip.